THU0600 A CASE OF SYSTEMIC SCLEROSIS COMPLICATED BY RENAL CRISIS: POTENTIAL ETIOPATHOGENETIC ROLE OF CYTOMEGALOVIRUS AND TREATMENT. (2nd June 2020) - Palermo, A.; Galli, E.; Spinella, A.; Cocchiara, E.; Lumetti, F.; Klinowski, G.; Giovanella, S.; Manzini, C. U.; Salvarani, C.; Giuggioli, D.
Abstract : Background: Scleroderma renal crisis (SRC) is a rare complication of systemic sclerosis (SSc), which can be triggered by viruses, such as Cytomegalovirus (CMV). SRC presents as a new-onset accelerated-phase hypertension with/without rapidly progressive renal failure. Objectives: Here we describe the case of a patient developing SSc complicated by the appearance of SRC after a recent episode of acute Cytomegalovirus infection. Methods: A 66-year-old male was referred to our Scleroderma Unit in March 2019. He presented with widespread skin rash, exertional dyspnoea and peripheral oedemas. He reported a myocarditis due to CMV occurred in October 2018. Antibodies anti-CMV IgM were detected in his serum. The patient developed a progressive cutaneous involvement characterized by diffuse oedema, sclerosis and melanoderma. Subsequently, Raynaud's phenomenon, puffy hands and pitting scars occurred. Laboratory tests showed positive ANA in a titer of 1:640 in a nucleolar staining pattern. Additionally, persistence of anti-CMV IgM was found. Skin biopsy showed scleroderma-like finding. Nailfold capillaroscopy revealed a SSc pattern. Chest high resolution computed tomography displayed basal interstitial thickening and subpleuric ground-glass opacities. Therefore, the patient was diagnosed with SSc. Three weeks later he developed severe hypertension and a rapid, progressive renal impairment. Serum creatinine increased (up to 4.15 mg/dl), glomerular filtration rate impaired (25 ml/min). Renal biopsy (picture A, B) revealed acute thrombotic microangiopathy. A diagnosis of thrombotic thrombocytopenic purpura was excluded. The patient was diagnosed with SRC and we started therapy with ACE-inhibitor and loop diuretic. Even if the dosage of ACE-inhibitor was increased up to the maximum tolerate dose, his renal function did not improve and the blood pressure control was inadequate. Consequently, the patient underwent plasma exchange (PEx) sessions. Two weeks later there was an improvement of renal function and blood pressure normalized. Six months later the disease was controlled: glomerular filtration rate was 41 ml/min and blood pressure was within the normal range. The patient was treated with ACE-inhibitor and underwent fortnightly apheretic sessions. Treatment for scleroderma vasculopathy is ongoing. Results: Viral infections may be responsible for SSc. A brief interval between an acute viral infection and the onset of SSc may suggest CMV as a possible trigger for the disease. Similarly, other infectious agents could be involved in the multistep and multifactorial mechanism of SSc. This case sheds light on the potential and intriguing role of CMV in SSc. Moreover, it leads us to hypothesize a CMV possible direct role in sclerodermal kidney damage. Use of ACE-inhibitor significantly reduced the mortality rate due to this complication. Exact therapeutic mechanism of PEx in the treatment of SSc is unclear. Conclusion: In our case the integrated ACE-inhibitor-PEx approach has showed effectiveness and safety in the management of SRC. References: [1]Ferri C, et al. Viral infections and systemic sclerosis. Clin Exp Rheumatol. 2014 32 (6Suppl86), S-229. [2]Zanatta E, et al. Therapy of scleroderma renal crisis: State of the art. Autoimmunity Rev. 2018 Sep;17(9):882-889. Disclosure of Interests: None declared